Role of Essential Oils of Some Higher Plants in Management of Food-borne Pathogenic Bacteria - Mishra, A. K. (American Journal of Botany and Bioengineering, 2024)
Five food grade plants were used to extract essential oils for screening against three food-borne human pathogenic bacteria, namely Bacillus cereus, Enterococcus faecalis and Escherichia coli. Preliminary studied were performed by disc diffusion method which showed diverse result. Basil oil was found to be efficient against all tested bacteria exhibiting higher effectiveness against B. cereus (51.10±5.46) and E. faecalis (44.47±4.52) while, canum oil-controlled E. coli (37.63±6.33). During dilution studies, Ocimum basilicum oil was found to be prominent as zone of inhibition was persisted and comparable after dilution. MIC evaluation by broth microdilution technique, basil oil was found to be exceedingly effective against amoxicillin resistant E. faecalis (MIC 2.0 µl/ml), while unproductive against E. coli (MIC 16.0 µl/ml). These values were comparable with that of used reference antibiotics namely; amoxycillin, ceftriaxone and kanamycin.